Catastrophic health expenditure and its determinants in households with gastrointestinal cancer patients: evidence from new health system reform in Iran. Issue 4 (29th August 2019) - Piroozi, Bakhtiar; Zarei, Bushra; Ghaderi, Bayazid; Safari, Hossein; Moradi, Ghobad; Rezaei, Satar; Ghaderi, Mahfooz; Amirhosseini, Shina; Mohamadi-Bolbanabad, Amjad
Abstract : Purpose: The right to health for all people means that everyone should have access to the needed healthcare services without suffering from severe financial hardship. The purpose of this paper is to investigate the prevalence as well as the effective factors on facing catastrophic health expenditures (CHE) among gastrointestinal cancer patients and families in Kurdistan province in west of Iran after the implementation of Health Transformation Plan (HTP). Design/methodology/approach: A cross-sectional study was carried out on 189 households with gastrointestinal cancer patients in Kurdistan province in 2018. Data were collected using World Health Survey questionnaire. A method developed by World Health Organization with the threshold of 40 percent household's capacity to pay was used in order to measure the proportion of households facing CHE. Also, logistic regression was applied for identifying the effective factors on household's exposure to CHE. Data were analyzed using STATA version 13. Findings: Almost 73 percent (72.7 percent) of the households ( n =117) faced the CHE. Not having supplementary health insurance (adjusted odds ratio (AOR): 3.8; 95% confidence interval: 1.3–10.8 (and having low socio-economic status (AOR: 7.1; 95% CI: 1.8–28.1) were the significant factors affecting the households' exposure to CHE. In total, 57 and 1 percent of the studied households reported that having a gastrointestinal cancer patient at home had a significant effect on refraining from using health services by other family members. Originality/value: The proportion of the studied households facing CHE was very high. This may indicate the weakness of health system as well as health insurance or the weakness of HTP in financial protection of fragile population.